2021
DOI: 10.5296/ije.v13i1.18289
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Translation? Students and the Hitches of Machine Translation of Academic Texts: Lecturers’ Perspectives

Abstract: Machine translation (MT) of academic texts is a trending phenomenon in the higher education context. Globalisation and internationalisation have seen a massive number of foreign students being admitted into higher education in countries where they study in the second or target language. Some of these students find it challenging to write a good academic text in the second language (i.e., English in the case of the United Kingdom). As a remedy, they resort to translating their work from the source text (ST) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…When people needed to translate the literature of other countries that they must read, many students used Google or machine translation. However, in this case, machine translation ignored the spirit contained in literary works [2]. De Vries Erik believed that there were many difficulties in computer text translation and evaluated the applicability of machine translation to literary translation.…”
Section: Related Workmentioning
confidence: 99%
“…When people needed to translate the literature of other countries that they must read, many students used Google or machine translation. However, in this case, machine translation ignored the spirit contained in literary works [2]. De Vries Erik believed that there were many difficulties in computer text translation and evaluated the applicability of machine translation to literary translation.…”
Section: Related Workmentioning
confidence: 99%
“…RA also reported that some students can try to change the wordings of an outsourced essay by using synonyms. However, in such instances, the essay will not usually make sense as inappropriate translations can distort the whole meaning of a sentence [9].…”
Section: Fig 4 Comparison Between As and Snmentioning
confidence: 99%
“…Data was collected in 2018 as part of a pilot study for a doctoral study in education which sought to understand the experiences of lecturers and students on the effects of language and culture on students' academic achievement. Two peerreviewed papers have been previously published from that study [8,9]. This is the third and final paper to be written from that dataset.…”
Section: Introductionmentioning
confidence: 99%